2021
DOI: 10.3389/fpubh.2021.713487
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Trends and Hotspots Regarding Clinical Research on COVID-19: A Bibliometric Analysis of Global Research

Abstract: Purpose: The coronavirus disease 2019 (COVID-19) outbreak, which began in December 2019, has not been completely controlled; therefore, COVID-19 has received much attention from countries around the world. Many related clinical studies, such as clinical trials, have been published, but to the knowledge of the authors, there has been no bibliometric analysis of these publications focusing on clinical research studies on COVID-19.Methods: Global publications on COVID-19 from January 2020 to December 2020 were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…CiteSpace was used to detect the mutation rate of keywords and generate a keyword ranking table with a high mutation rate. In the network graph, different nodes represent various elements, such as authors, institutions, countries, and keywords, whereas the size of nodes reflects the number or frequency of publications, and the connections between nodes represent relations such as cooperation, cooccurrence, or cocitation (23,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…CiteSpace was used to detect the mutation rate of keywords and generate a keyword ranking table with a high mutation rate. In the network graph, different nodes represent various elements, such as authors, institutions, countries, and keywords, whereas the size of nodes reflects the number or frequency of publications, and the connections between nodes represent relations such as cooperation, cooccurrence, or cocitation (23,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the production of each country, India is the country with the highest number of publications; however, it is China that presents the highest number of citations, which could indicate a greater impact worldwide. Something relevant to mention is that although China is one of the leaders in COVID-19 research and its different topics, 21 , 22 , 23 this is not the case in the dental field. This is in line with a previous bibliometric study that reported that China did not have the highest output on the dental and COVID-19 topic between 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…A bibliometric approach has been adopted for the analysis of the coronavirus disease 2019 (COVID-19) (Xia et al, 2021 ). However, no studies have focused on the gastrointestinal microbiome, human gastrointestinal microbiome, or gut microbiome in obesity (Yao et al, 2018 ; Huang et al, 2019 ; Yuan et al, 2021 ) and the interaction between gut microbiota and immune system.…”
Section: Introductionmentioning
confidence: 99%